Topological Control of Columnar Stacking Made of Liquid‐Crystalline Thiophene‐Fused Metallonaphthalocyanines - Suzuki, Hiroyuki (ChemistryOpen, 2015)
The spontaneous organization of two‐dimensional polyaromatic molecules into well‐defined nanostructures through noncovalent interactions is important in the development of organic‐based electronic and optoelectronic devices. Two regioisomers of thiophene‐fused zinc naphthalocyanines ZnTNc(endo) and ZnTNc(exo) have been designed and synthesized to obtain photo‐ and electroactive liquid crystalline materials. Both compounds exhibited liquid crystalline behavior over a wide temperature range through intermolecular π–π interactions and local phase segregation between the aromatic cores and peripheral side chains. The structural differences between ZnTNc(endo) and ZnTNc(exo) affected the stacking mode in self‐assembled columns, as well as symmetry of the two‐dimensional rectangular columnar lattice. The columnar structure in liquid crystalline phase exhibited an ambipolar charge‐transport behavior.